Vibration analysis of the continuous beam bridge considering the action of jump impacting. Issue 13 (October 2022) - Liu, Yang; Yan, Wanli; Yin, Xinfeng; Wang, Lei; Han, Yan
In the existing vehicle-bridge coupling vibration analysis, the vehicle model was mostly coupled with the bridge node by interpolation methodology, therefore, it was difficult to accurately consider the bridge vibration response under the condition of vehicle-bridge separation. In order to further study the effect of vehicle jumping impact on the vehicle-bridge coupling vibration system, a model which can describe the vehicle jumping impact process is established based on a designed integrated simulation platform with the interface contact algorithm. The effects of jumping impact on wheel contact force and bridge vibration displacement response were studied under two parameters including jumping height and vehicle speed. The simulation results show that the vehicle-bridge coupling vibration considering the action of the vehicle jump impacting can be effectively analyzed and the wheel contact forces/displacements are significantly affected by the jumping height.